1998
DOI: 10.1089/hyb.1998.17.339
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mdm-2 Protein in Neoplastic, Preneoplastic, and Normal Bronchial Mucosa Specimens: Comparative Study with p53 Expression

Abstract: Loss of function of the p53 tumor supressor gene is involved in nearly all human cancer. Recently a cellular oncogene product, mdm2, has been shown to bind to p53 and eliminate its ability to function as a transcription factor. mdm2 and p53 immunohistochemical protein expression was studied in tumor tissues, preneoplastic lesions, and normal bronchial mucosa. The specimens were obtained during diagnostic bronchoscopy from 53 patients with lung cancer. In the tumor specimens, p53 nuclear staining was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…The current study is the first to assess MDM2 protein overexpression at every stage of SQCC development. Previously, MDM2 expression has been detected in some cases of hyperplasia, metaplasia and dysplasia, but the proportion of lesions expressing MDM2 was not determined nor compared with normal tissue expression [14]. MDM2 was initially overexpressed at the MiD stage in the current study, with 80% of the biopsies showing a high MDM2 expression, compared with only 19% of normal bronchial tissue.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The current study is the first to assess MDM2 protein overexpression at every stage of SQCC development. Previously, MDM2 expression has been detected in some cases of hyperplasia, metaplasia and dysplasia, but the proportion of lesions expressing MDM2 was not determined nor compared with normal tissue expression [14]. MDM2 was initially overexpressed at the MiD stage in the current study, with 80% of the biopsies showing a high MDM2 expression, compared with only 19% of normal bronchial tissue.…”
Section: Discussioncontrasting
confidence: 53%
“…Indeed, MDM2 and p14arf have been widely studied in invasive lung cancer [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. However, limited data suggest that MDM2 expression is modified in the early stages of carcinogenesis [14], while p14arf has not been assessed in bronchial pre-invasive tissues. To the current authors' knowledge, NPM expression has not been studied in lung cancer, either at invasive or early stages.…”
mentioning
confidence: 99%
“…27) No association was found between the expressions of p53 and MDM2 in colorectal and bronchial neoplasms. 28,29) In this study, it was found that the MDM2 overexpression was not significantly associated with either p53 expression or the absence of p53 gene mutation in oral SCC. These findings suggest that p53-independent mechanisms may also be important in oral SCC, and that MDM2 expression may not be specifically linked to the functional status of p53.…”
Section: Discussionmentioning
confidence: 57%
“…The protein MDM-2 binds to p53 and eliminates its ability to function as a transcription factor. Alterations in MDM-2 expression have been found in preneoplastic lesions [47]. Other authors have found an apparent deregulation of the p53 apoptosis transcription pathway in precursor bronchial lesions of lung cancer.…”
Section: Data Supporting the Preneoplastic Nature Of Lesionsmentioning
confidence: 99%